2012
DOI: 10.1515/polyeng-2012-0042
|View full text |Cite
|
Sign up to set email alerts
|

The influence of level of interfacial healing on the weld-line strengths of injection molded parts

Abstract: Weld lines are commonly present within injection-molded plastic components and generally reduce strength. In designing a plastic part, the designer can often vary the wall thicknesses, or move the gate locations to position the weld line, so that its structural loading is minimized. By altering such variables as melt temperature, mold temperature, and packing pressure, slight increases in weld-line integrity can be achieved. These approaches often do not increase the part strength or performance to an acceptab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…Correlations of the viscosity or temperature profile in the weld line with the weld line strength were found. [18,27,28] However, these only allow a qualitative prediction of the weld line strength, which can only be used to a very limited extent as a basis for part design.…”
Section: Prediction Of Weld Lines With Injection Molding Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlations of the viscosity or temperature profile in the weld line with the weld line strength were found. [18,27,28] However, these only allow a qualitative prediction of the weld line strength, which can only be used to a very limited extent as a basis for part design.…”
Section: Prediction Of Weld Lines With Injection Molding Simulationmentioning
confidence: 99%
“…Explanation approaches are the relaxation of the strongly oriented molecules or air inclusions in the weld line. [1,[16][17][18][19]…”
Section: Introductionmentioning
confidence: 99%
“…Die Bildung einer V-förmigen Nut, welche aufgrund ihrer Kerbwirkung unter Belastung zu einer Spannungskonzentration in der Bindenaht führt, wird in der Literatur mehrmals beschrieben [10,11]. Die Ursache für die Entstehung dieser V-Nut ist derzeit noch nicht vollständig geklärt [12][13][14]. Mögliche Ursachen sind Lufteinschlüsse [2,14,15] oder eine lokal höhere Volumenschwindung in Richtung der molekularen Orientierungen [3,16].…”
Section: Bindenähte In Spritzgiessbauteilenunclassified
“…Katsuyuki et al 2 have reported research on the characterization of the microstructure using polarized laser Raman spectroscopy, micro-cutting analysis, and fracture testing and found significant reduction by weld-line attributed to increasing molecular weight or broadening molecular weight distribution. Chung-Ching Huang et al 9 developed a hot runner system, sequential valve gates aimed to achieve cost effective methods for the prediction of weld-line properties. The authors have predicted the strength of the weld-line using the temperature of the melt front as suggested by mold flow simulation software.…”
Section: Introductionmentioning
confidence: 99%
“…stress at break or strain at break will not be the right approach. 1,5,8,9 This may lead to the wrong design and subsequent failure of the part. To avoid this, it becomes necessary while designing a plastic injection molded part to identify the weld-line areas and strength of part near weld-line areas.…”
Section: Introductionmentioning
confidence: 99%